Periodontitis in First Degree-Relatives of Individuals With Rheumatoid Arthritis: A Short Narrative Review - Zekeridou, Alkisti; Gilbert, Benoit; Finckh, Axel; Giannopoulou, Catherine (Frontiers in Oral Health, 2022)
Periodontal disease (PD) and rheumatoid arthritis (RA) are chronic inflammatory diseases with a bi-directional relationship. Both share common genetic and environmental risk factors and result in the progressive destruction of bone and connective tissue. First degree relatives of patients with RA (FDR-RA) are one of the at-risk populations for RA. The etiopathogenic mechanisms of their susceptibility are currently being explored, focusing mostly on the role of anti–cyclic citrullinated protein/ peptide antibodies (ACPA) in triggering RA. Oral microbiota and their relation with oral health has been suggested as a factor influencing the risk of the FDR-RA developing RA. In particular, compromised periodontal status often correlates with ACPA seropositivity in FDR-RA. The presence of periodontal pathogens such as Porphyromonas gingivalis, in oral microbiota has been proposed to increase the risk of developing RA through its uniquely expressed peptidyl arginine deiminase (PPAD), capable of citrullinating both host and bacterial peptides. Aggregatibacter actinomycetemcomitans and its leukotoxin A (LtxA), also induces hypercitrullination in host neutrophils. Common risk factors of periodontitis and RA such as genetic predisposition, smoking, higher local and systemic inflammatory burden, are discussed in the literature. Based on those mechanisms periodontal disease seems to be presented as one of the factors triggering RA in FDR-RA. Larger studies evaluating all the potential mechanisms linking RA and periodontitis are needed in FDR-RA to confirm that periodontal disease should be considered in the screening of FDR-RA.